Relationship of Parent Parenting With Children's Social Development in Jorong Kampung VII Kec. South Rao Pasaman Regency - Sisri Landa Sari; Indra Jaya (Prodi. Pendidikan Islam Anak Usia Dini, Institut Pesantren KH. Abdul Chalim, 2020)
This research is based on the still weak socialization of children with the surrounding environment, not being able to get along, and more happy with personal activities. This study aims to: (1) describe parenting, (2) describe the child's social development, and (3) examine the relationship between parenting and social development of children. This research uses a quantitative method with a descriptive correlational analysis approach. parents who have children aged 4-6 years in Jorong village VII Kec. South Rao Pasaman Regency, amounting to 61. A total of 53 people were selected using the Slovin formula. The research instrument used was parenting and the child's social development questionnaire. Data analysis techniques are descriptive and correlational tests. To facilitate data analysis, researchers used SPSS Version 20. The results of the study revealed that (1) the parenting style of the category was moderate (2) the social development of the child was in the medium category, and (3) there was a significant relationship between parenting style and the social development of the child with a correlation coefficient of 0.350 at a significance level of 0.010 with a very strong relationship level. Based on research findings, parents are advised to be able to choose and use good, appropriate, and balanced parenting, and can have a good impact and contribution to the social development of children.